Perilaku Berbasis Teknologi di Sosial Media pada Digital Nattive - Laelatus Syifa Sari Agustina (Journal An-Nafs: Kajian Penelitian Psikologi, 2020)
Social media has become a new way for people to communicate with others. Social media is media on the internet that allows users to present themselves, work together, share, communicate with other users form social bonds virtually, and express themselves. Their identity is built by offline and online interaction. This condition makes its uniqueness when someone behaves in communicating and expressing themselves on social media. This study aims to describe internet-based behavior on digital natives, especially in posting content on social media. This research used a descriptive qualitative method, through structured interviews with 84 students aged 18-23 years, male and female gender. The data obtained analyzed by coding. The results show that the media gives satisfaction and makes them survive to use it actively and provides the availability of information, entertainment, and connection with their social life. Feelings of insecurity in using social media are closely related to the social consequences that will get and manifested through restrictions on access is allowed to view account content. The purpose of posting is different, but many illustrate needed for self-expression and desire to provide social influence in the form of direct feedback or the delivery of their thoughts to fellow users.